Creative Inclusive Empowerment Model for Persons with Disabilities in Rural Areas: Integrating Institutional Support, Skill Development, and Market Access - Tiara Widya Antikasari; Eny Supriati; Alwan Wibawanto (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study addresses the gap in the literature on disability empowerment by proposing a creative economy-based empowerment model that integrates institutional support, skill development, and multi-stakeholder collaboration in rural contexts. Using a qualitative approach, data were collected through in-depth interviews, observations, Focus Group Discussions (FGDs), and documentation. The findings reveal a three-tier empowerment structure (daily, monthly, and annual income programs) supported by LKS Rumah Harapan Mulya as the central institutional platform. This study proposes a Creative Inclusive Empowerment Model consisting of four components: institutional support, adaptive skill development, creative production, and market integration. Theoretically, this study extends empowerment theory by demonstrating that institutionally-driven, multi-stakeholder models yield more sustainable outcomes than individually-focused approaches. Practically, the model offers a scalable framework for inclusive rural development that can be adapted by local governments and community organizations. This research employs a qualitative field research approach. Data were collected through in-depth interviews, observations, Focus Group Discussions (FGD), and documentation. A purposive sampling technique was applied to select 15–20 key informants, including persons with disabilities, village officials, and relevant stakeholders. Data validity was ensured through source triangulation, method triangulation, and theory triangulation. The findings show that economic empowerment for persons with disabilities is structured through three main programs organized by LKS Rumah Harapan Mulya: daily income through handicraft production (doormats, splash batik, and prayer beads), monthly income through livestock and agricultural activities, and annual income through goat farming. These activities are supported by adaptive skill training, institutional mentoring, and multi-channel marketing strategies. This study contributes a Creative Inclusive Empowerment Model that highlights the critical role of institutional frameworks and stakeholder collaboration in achieving sustainable economic inclusion for persons with disabilities in rural areas.